Ethanol and glycerol green emulsifying solvent for the formation of a Lavandula stoechas essential oil/β-cyclodextrin inclusion complex: mixture design and adulticidal activity against Culex pipiens. Issue 8 (August 2022) - Ez-zoubi, Amine; Ez zoubi, Yassine; Ramzi, Amal; Fadil, Mouhcine; El Ouali Lalami, Abdelhakim; Farah, Abdellah
Abstract: The purpose of this study is to investigate the effect of essential oil medium on the inclusion complex of L. stoechas EO in β-cyclodextrin, as well as to examine the impact of the encapsulating action on the adulticidal activity. In line with this, L. stoechas EO was hydrodistilled and determined through GC-MS. Furthermore, the optimization of EO medium was conducted using a binary mixture design of ethanol and glycerol as green emulsifier solvent. Fourier transform infrared spectroscopy, scanning electron microscopy, X-ray powder diffraction and thermogravimetric analysis were used to verify the establishment of the IC. The insecticidal effect of the created formulation was evaluated against C. pipiens female mosquitoes. The optimum ethanol: glycerol ratio was 0.73: 0.27, corresponding to 58.86% of encapsulation efficiency. The fumigant test showed that, after 24 h of exposure, L. stoechas EO exerted only 24.56 ± 1.04%, while the encapsulated oil killed 57.89% of the adult population. At the highest dose (312.5 μl/L), the encapsulated oil provided the most significant effect on adults (100% mortality after 54 h) compared to non-encapsulated oil (100% mortality after 72 h). The encapsulated form of L. stoechas EO constitutes a promising alternative for the control of mosquitoes that are responsible for human diseases. Highlights: Camphor, fenchone, camphene, linalool, 1, 8 cineole, borneol, and α-pinene represented the main compounds in L. stoechas EO. The mixture design between ethanol and glycerol as green emulsifiant allowed for improvement of the encapsulation efficiency. The FTIR, SEM, PXRD and TGA were confirmed the processes of inclusion complex. The encapsulation of L. stoechas EO by β-cyclodextrin was accompanied by the increase of thermal stability and adulticidal activity. Abstract : Lavandula stoechas, Inclusion complex, β-Cyclodextrin, Mixture design, Insecticidal activity, Culex pipiens